Effect of Temperature and Drying Time on the Synthesis of Stable K2FeO4 By Wet Method - El Maghraoui, Abdellatif; Zerouale, Abdelaziz; Ijjaali, Mustapha (International Journal of Chemistry and Materials Research, 2015)
Fe (VI) as an oxidant has a higher oxidation potential than ozone, hydrogen peroxide, permanganate or chlorine.Demanding environmental regulations encourage the use of ferrate as a decontaminating agent of choice. Thus, the purpose of this work is to identify and optimize the time and drying temperature of stable to ambient K2FeO4 by wet means facilitating their storage and transport. Wet synthesis is performed by attacking ferric sulfate FeSO4, 7H2O by ClO- hypochlorite with a chlorometric degree of 50 ° F in a concentrated medium KOH, at a temperature of 55 ° C. The drying time is of the order of 12 hours at a temperature of 120 ° C. The obtained result was characterized by UV spectrophotometer by measuring the optical density at a wavelength of 507 nm.